Pathways of Children Reported for Domestic and Family Violence to Australian Child Protection. Issue 4 (2nd October 2019) - Shlonsky, Aron; Ma, Jennifer; Jeffreys, Colleen; Parolini, Arno; Katz, Ilan
ABSTRACT: Child protection systems often contend with domestic and family violence (DFV) as a maltreatment concern, yet few large-scale studies have explored how child protection services (CPS) systems respond to DFV compared with other concerns. Secondary longitudinal analysis of administrative data from three Australian State CPS systems finds that the number of DFV reports increased faster than notifications for other concerns, and children reported for DFV also tended to be reported for emotional and physical abuse. Children reported for DFV were slightly less likely to transition from report to formal child maltreatment investigation. Overall, system responses to maltreatment concerns appear to be similar across concern types despite substantial differences in their aetiologies and options for effective interventions. IMPLICATIONS: Future CPS policy and practice development should involve consideration of the specific aetiologies and service needs of each type of maltreatment concern, and the CPS response should reflect these differences. Information about the specific service response (e.g., intervention type, quality, and extent of services) should be collected and used to inform improvements in the CPS system. Data linkages between systems should be strongly considered in order to monitor and improve multisystem service responses to DFV.